Decreased Immunoreactivities and Functions of the Chloride Transporters, KCC2 and NKCC1, in the Lateral Superior Olive Neurons of Circling Mice - Pradhan, Jonu; Maskey, Dhiraj; Park, Ki Sup; Kim, Myeung Ju; Ahn, Seung Cheol (Clinical and experimental otorhinolaryngology, 2011)
We tested the possibility of differential expression and function of the potassium-chloride (KCC2) and sodium-potassium-2 chloride (NKCC1) co-transporters in the lateral superior olive (LSO) of heterozygous (+/cir) or homozygous (cir/cir) mice. Mice pups aged from postnatal (P) day 9 to 16 were used. Tails from mice were cut for DNA typing. For Immunohistochemical analysis, rabbit polyclonal anti-KCC2 or rabbit polyclonal anti-NKCC1 was used and the density of immunolabelings was evaluated using the NIH image program. For functional analysis, whole cell voltage clamp technique was used in brain stem slices and the changes of reversal potentials were evaluated at various membrane potentials. Immunohistochemical analysis revealed both KCC2 and NKCC1 immunoreactivities were more prominent in heterozygous (+/cir) than homozygous (cir/cir) mice on P day 16. In P9-P12 heterozygous (+/cir) mice, the reversal potential (E(gly)) of glycine-induced currents was shifted to a more negative potential by 50 µM bumetanide, a known NKCC1 blocker, and the negatively shifted E(gly) was restored by additional application of 1 mM furosemide, a KCC2 blocker (-58.9±2.6 mV to -66.0±1.5 mV [bumetanide], -66.0±1.5 mV to -59.8±2.8 mV [furosemide+bumetanide], n=11). However, only bumetanide was weakly, but significantly effective (-60.1±2.9 mV to -62.7±2.6 mV [bumetanide], -62.7±2.6 mV to -62.1±2.5 mV [furosemide+bumetanide], n=7) in P9-P12 homozygous (cir/cir) mice. The less prominent immunoreactivities and weak or absent responses to bumetanide or furosemide suggest impaired function or delayed development of both transporters in homozygous (cir/cir) mice.